Potential of hospital wastewater treatment using locally isolated Chlorella sp. LH2 from cocoon wastewater - Lê, Thị Anh Tú (2024)
Chlorella sp. is able to grow and transform inorganic and organic contaminants in wastewater to create biomass. In the present study, Chlorella sp. LH2 isolated from cocoon wastewater was able to thrive in hospital wastewater, then remove nutrients and eliminate E. coli ATCC 8739. The results indicated that optimal cultivation conditions of Chlorella sp. LH2 in hospital wastewater were pH of 8, light:dark cycle of 16:8 at 30oC. The inhibitory effect of chlorination on algae growth was accompanied with the chlorine concentration. BOD5:COD ratio of 0.77 indicated biodegradability of hospital wastewater. The untreated and treated wastewatee samples were collected to investigated the nutrient removal efficiency after 10 days. Untreated and treated results were192 ± 8.62 mg/l 23.91 ± 2.19 mg/l for BOD5; 245 ± 9.15 mg/l and 47.31 ± 5.71 mg/l for COD. The treated value met the required standards for hospital wastewater treatment. The removal efficiency total nitrogen and total phosphorus were 68.64% and 64.44% after 10 days, respectively. Elimination of E. coli ATCC 8739 after 7 days by Chlorella sp. LH2 was 88.92%. The results of this study suggest the nutrients and pathogens removal potential of Chlorella sp. LH2 in hospital wastewater for further practical applications.